INVESTIGATION OF MODIFICATION PROCESSES IN RESPECT OF WEAR-RESISTANT PLASMA COATINGS USING PULSE-PLASMA MACHINING - V. A. Okovity; F. I. Panteleenko; А. F. Panteleenko; V. V. Okovity; A. I. Shevtsov; A. F. Iliouschenko; V. M. Astashinsky (Наука и техника)
The paper contains information on the investigated processes and optimized technological parameters  of  highly-energy  machining of plasma  coatings  made  of  cladding  composite  powders obtained as a result of self-spreading high-temperature synthesis. Metallographic analysis has been carried out and coating properties machined at optimum regimes have been investigated in the paper